Application of the C.45 Algorithm in Measuring the Satisfaction Level of Hotel Visitors - Rosmalina Purba; Fricles Ariwisanto Sianturi (DISTANCE: Journal of Data Science, Technology, and Computer Science, 2021)
Hotel visitor satisfaction is one of the most important things in assessing the level of service by the hotel to its visitors. The purpose of this study was to determine the satisfaction of hotel visitors based on service criteria (very good, good, good enough, not good), facilities (good, pretty good, not good), quality (high, medium), and classification (first class, business, economy) hotel rooms by applying the C.45 Algorithm method. to visitors who expressed satisfaction or dissatisfaction. In The Crew Hotel, the criteria have not been measured with certainty, so the management is still manually determining visitor satisfaction so it is less effective. Thus, the author tries to measure the four criteria by applying the processing of the questionnaire dataset given to visitors, when staying, either in writing or asking visitors. using the C4.5 algorithm in measuring the level of satisfaction of visitors to The Crew so that a decision tree is formed. to advance the development of The Crew Hotel and improve service at the hotel. After the calculation is done manually, then the proof is done using an application designed by the author according to the existing rules.